Detoxification of sewage sludge by natural attenuation and implications for its use as a fertilizer on agricultural soils - Mazzeo, Dânia Elisa Christofoletti [UNESP] (2016)
Sewage Sludges (SS) from wastewater treatment systems constitute a potential alternative to agricultural fertilizers. However, their use is limited by the presence of toxic substances that may represent significant hazards for the environment and for human health. To test the potential of natural processes to attenuate their putative toxic activities, actual SS samples from domestic sewage were buried in holes in a pollution-free environment for different periods of time, up to one year. Aqueous and organic extracts were obtained after each period of natural attenuation, and their respective toxicity was tested for estrogenic and dioxin-like activity by yeast-based bioassays (ER-RYA and AhR-RYA, respectively) and for general toxicity and teratogenicity in zebrafish embryos. Dioxin-like activity was also tested in zebrafish embryos by monitoring the induction of the marker gene cyp1a. Whereas the results showed essentially no estrogenic activity, both dioxin-like activity and embryotoxicity were observed in the initial samples, decreasing significantly after six months of attenuation. Chemical analysis of toxic SS samples showed the presence of low levels of dioxins and furans, and relatively high levels of m- and p-cresol, at concentrations that only partially justify the observed biological effects. Our data indicates the presence of largely uncharacterized hydrophilic compounds with high biological activity in SS, constituting a potential risk of groundwater pollution upon their disposal into the environment. It also shows that this potential impact may be significantly mitigated by attenuation protocols, as the one presented here.